Promoting cardioprotection with fenugreek: Insights from CoCl2 -induced hypoxia in neonatal rat cardiomyocytes - Hanafi, Noorul Izzati; Mohamed, Maizan; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Saidan, Noor Hafizoh; Hua, Gan Siew; Abdul Kadir Pahirulzaman, Khomaizon; Rao, Pasupuleti Visweswara (University of Medical Sciences, 2023)
Objective(s): This study aimed to investigate the protective effects of fenugreek on CoCl2 -induced hypoxia in neonatal rat cardiomyocytes. Materials and Methods: Primary cardiomyocytes were isolated from Sprague Dawley rats aged 0–2 days and incubated with various concentrations of fenugreek (10-320 µg/ml) and CoCl2 -induced hypoxia for different durations (24, 48, and 72 hr). Cell viability, calcium signaling, beating rate, and gene expression were evaluated. Results: Fenugreek treatments did not cause any toxicity in cardiomyocytes. At a concentration of 160 µg/ml for 24 hr, fenugreek protected the heart against CoCl2 -induced hypoxia, as evidenced by reduced expression of caspases (-3, -6, -8, and -9) and other functional genes markers, such as HIF-1α, Bcl-2, IP3R, ERK5, and GLP-1r. Calcium signaling and beating rate were also improved in fenugreektreated cardiomyocytes. In contrast, CoCl2 treatment resulted in up-regulation of the hypoxia gene HIF-1α and apoptotic caspases gene (-3, -9, -8, -12), and down-regulation of Bcl-2 activity. Conclusion: Fenugreek treatment at a concentration of 160 µg/ml was not toxic to neonatal rat cardiomyocytes and protected against CoCl2 -induced hypoxia. Furthermore, fenugreek improved calcium signaling and beating rate and altered gene expression. Fenugreek may be a potential therapeutic agent for promoting cardioprotection against hypoxia-induced injuries